Marketing and sustainability from the perspective of future decision makers - D. Pantelic (South African Journal of Business Management, 2016)
Contemporary research on sustainability is fragmented between multiple disciplines and areas, with on-going debates about methodological as well as practical issues. The core value of sustainability is embedded in the long-term maintenance of quality of life and contains environmental, economic and social components. Business organizations have a substantial responsibility for preserving the quality of life for future generations, as a result of the role they play in transforming natural and societal resources into goods and services. The marketing function is a major force in strategic decision-making in contemporary organizations. With its arsenal of tools for influencing (managing) consumption patterns, marketing must take responsibility for sustainable behaviour of both organizations and consumers. This article discusses the role of marketing in facilitating sustainable behaviour. Contemporary marketing education may not prepare students to use marketing’s influence to support sustainability. This study, using senior level Marketing students, assesses the perceptions, opinions and attitudes towards sustainability at three different universities in Austria, Portugal and Serbia. These students represent future decision makers shaping marketing and business strategies. The results of this research inform the marketing academic community about its ability to build contemporary curricula, as well as marketing professionals who seek justification for sustainable marketing strategies. Business schools, in their role of educators, should assume more active role in shaping students’ attitudes towards sustainability.